Corpo and Corpus: Paranoid and Reparative Writing in Sibilla Aleramo's Una donna and Il passaggio. (2nd January 2018) - Valisa, Silvia
Abstract : This essay considers the ending of Sibilla Aleramo's Una donna (1906) in terms of its much-discussed fictionalization of autobiographical material. It then highlights the narrative and literary (dis)continuity that exists between the ending and the book that followed, Il passaggio (1919). Arguing that we can read the movement from Una donna to Il passaggio in terms of a hermeneutical shift from suspicion, in Ricoeur's terms, to a reparative position, to use Sedgwick's phrase, this essay envisions as fundamental to Aleramo the possibilities inscribed in narrative, the power to move (and remove) one's body [ corpo ] from the materiality assigned to women by patriarchy, and to reinsert it within a citational economy of trust in the written word [ corpus ] and the written word's surprises.